ORGANIZING ICT-SUPPORTED WORKSHOPS AT UNIVERSITIES - Shulska, Nataliia M.; Matviichuk, Nataliia M.; Hromyk, Yuriy V.; Kolenda, Nataliia V.; Rymar, Nataliia Yu (Information technologies and learning tools, 2017)
The article systematizes theoretical and practical experience of organizing classes in the format of dynamic training using the technology of the workshop in higher educational institutions. The emphasis is placed on the peculiarities of the use of integrated workshops with technical (computer) support during classes, as well as remote workshops for the organization of students’ independent work. The practical experience of organizing dynamic training in the form of the workshop for students of Journalism with the use of both an integrated «training workshop» and the possibilities of a free training platform «Prometheus» is presented. Based on the questionnaire of the participants in the training group, the advantages of using the technology of the workshop in the educational process are determined. В статье систематизирован теоретический и практический опыт организации занятия в формате динамического обучения с использованием технологии воркшопа в вузе. Акцентировано внимание на особенностях применения интегрированных воркшопов с техническим (компьютерным) сопровождением во время проведения занятий, а также дистанционных воркшопов для организации самостоятельной работы студентов. Представлены собственный практический опыт организации динамического обучения в формате воркшопа для студентов журналистских специальностей с применением как интегрированной «учебной мастерской», так и возможностей бесплатной учебной платформы «Prometheus». На основе анкетирования участников учебной группы определены преимущества использования технологии воркшопа в учебном процессе. У статті систематизовано теоретичний і практичний досвід організації заняття у форматі динамічного навчання з використанням технології воркшопу у ВНЗ. Акцентовано увагу на особливостях застосування інтегрованих воркшопів з технічним (комп’ютерним) супроводом під час проведення занять, а також дистанційних воркшопів для організації самостійної роботи студентів. Представлено власний практичний досвід організації динамічного навчання у форматі воркшопу для студентів журналістських спеціальностей із застосуванням як інтегрованої «навчальної майстерні», так і можливостей безкоштовної навчальної платформи «Prometheus». На основі анкетування учасників навчальної групи визначено переваги використання технології воркшопу у навчальному процесі.